An analytical study of maternal death at tertiary care hospital - Goswami, K D; Dudhrejia, K M; H. Parmar, Prakash; Kataria, Arvind (International Journal of Medical Research and Review, 2015)
Background: Maternal mortality is one of the important public health challenges faced by India today. Being a country with highest number of maternal deaths worldwide, i.e. 63, 000 per year and having a Maternal Mortality Ratio of 230/1,00,000 live births, it is a matter of grave concern and high priority. Objective: To study the MMR and common causes leading to death, so that improving maternal health and reducing maternal mortality rate significantly. Methods: We have done Retrospective Observational study in Department of Obstetrics & Gynecology, P.D.U. Medical College, Rajkot between 1st August 2012 to 31st July 2014. Results: There were 30 Maternal Deaths during Study Period of 2 years in the Institute. Maternal Mortality Ratio of the Study Centre was 219 per lakhs live births. Out of 30 maternal deaths 21-30 yrs age group having 77% of maternal death while 67% belongs to lower socio-economical class. Out of 30, 15 (50%) died within 24 hrs of delivery. Hemorrhage was the most common cause in 15(50%) cases while others were Eclampsia (13%), septicemia (11%), ARDS (13%), others (13%). Conclusions: Maternal Mortality Ratio of the Study Centre was 219 per lakhs live births. Hemorrhage was the most common cause. Early registration, regular antenatal care, early referral are key things in reduction of maternal deaths. Facility based maternal death review (FBMDR) should be done at every institute level to find out the deficit and thus helping in reduction of maternal deaths.